2005
DOI: 10.1021/cm051064h
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Infrared Spectroscopy and Density Functional Theory Modeling of Hafnium Alkylamine Adsorption on Si−OH and Si−H Surfaces

Abstract: In-situ attenuated total internal reflection infrared spectroscopy has been used to examine initial adsorption and reaction steps in atomic layer deposition of HfO 2 from tetrakis(diethylamino) hafnium (TDEAHf) on SiO 2 and hydrogen-terminated Si(100) surfaces. At low deposition temperatures (25-250 °C), TDEAHf directly reacts with the Si-H surface, resulting in partial removal of Si-H bonds and formation of a four-membered Si-O-Hf-Si bonding structure that can rapidly oxidize. The hydrogen removal process is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 20 publications
6
65
1
Order By: Relevance
“…For example, the work of the groups of Kelly et al suggested that the oxygen impurities play a crucial role in the interface formation when aluminum oxide deposition is attempted on H-passivated Si(100) substrate [453]. A similar conclusion was reached by the analysis of hafnium alkylamine adsorption on H-covered Si (100) substrate by the groups of Musgrave and Parsons [454], where the reaction of tetrakis-(diethylamino)-hafnium was deemed unlikely on an ideal H-terminated Si(100) surface. Thus, instead of an ideal interface that is often presented in the ALD schemes, the impurities, and not the plain surface, may play the determining role.…”
Section: First Attempts To Move Into the Third Dimensionmentioning
confidence: 82%
“…For example, the work of the groups of Kelly et al suggested that the oxygen impurities play a crucial role in the interface formation when aluminum oxide deposition is attempted on H-passivated Si(100) substrate [453]. A similar conclusion was reached by the analysis of hafnium alkylamine adsorption on H-covered Si (100) substrate by the groups of Musgrave and Parsons [454], where the reaction of tetrakis-(diethylamino)-hafnium was deemed unlikely on an ideal H-terminated Si(100) surface. Thus, instead of an ideal interface that is often presented in the ALD schemes, the impurities, and not the plain surface, may play the determining role.…”
Section: First Attempts To Move Into the Third Dimensionmentioning
confidence: 82%
“…55 Other groups have also considered the same basis set for describing the reactions of adsorption of organohafnium compounds on silicon. 56 Energies corresponding to selected structures optimized with the LANL2DZ basis set were compared to single-point calculations using a more expensive basis set, 6-311+G(d,p). Table 1 discussed below shows very good agreement between the two basis sets.…”
Section: Computational Detailsmentioning
confidence: 99%
“…[38,39] In particular, the adsorption of tetrakisdimethylamidohafnium, [Hf{NA C H T U N G T R E N N U N G (CH 3 ) 2 } 4 ] or TDMAH, on a hydrogen terminated SiA C H T U N G T R E N N U N G (100) surface has been studied by a combination of experimental and theoretical methods. [39] A room-temperature reaction is observed, but only to a limited extent and by using large doses of TDMAH. The ALD performed at 523 K with TDMAH and water shows that SiÀH species are present on a surface even after 100 reaction cycles at this temperature.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%